The molecular gas content of ULIRG type 2 quasars at z < 1 - Rodríguez, M.; Villar-Martín, M.; Emonts, B.; Humphrey, A.; Drouart, Guillaume; García Burillo, S.; Pérez Torres, M. (2014)
We present new results of CO(1-0) spectroscopic observations of four Sloan Digital Sky Survey (SDSS) type 2 quasars (QSO2) at z ~ 0.3, observed with the 30-m IRAM radio telescope. The QSO2 have infrared luminosities in the ultra-luminous infrared galaxies (ULIRG) regime. We confirm the CO(1-0) detection in one of our four QSO2, SDSS J1543-00, with L'CO and MH2 (1.2 ± 0.2) × 1010 K km s-1 pc2 and (9.4 ± 1.4) × 109 M ?, respectively. The full width at half maximum (FWHM) of the CO(1-0) line is =575 ± 102 km s-1. No CO(1-0) emission is detected in SDSS J0903+02, SDSS J1337-01, SDSS J1520-01 above 3 sigma, yielding upper limits on M(H2) ~ 9.6, 4.3 and 5.1 × 109 M?, respectively. We expand previous studies of the molecular gas content of intermediate z QSO2 into the ULIRG regime. Taking into account nine QSO2 at z ~ 0.3-1.0 from the literature, we discuss the location of the 13 ULIRG QSO2 at z < 1 with available L'CO measurements in the L'CO vs. z and L'CO vs. LFIR diagrams, in comparison with other QSO1 and ULIRG star forming samples. © ESO, 2014.